Formation of Social Activity of Students - Future Teachers of Physical Education - Abdrazakhovich, Zholdasbekov Abdimanap; Zhumabekov, Ruslan Kaldybekovich; Mukhamedzhan Taspolatovich, Erzhigit Mamraimovich Kurimbaev, (Opción, 1970)
The article discusses the rationale and technologies for the formation of social activity of a student-future teacher of physical education. Based on existing research, we distinguish the following components in the structure of the socially active position of future physical education teachers: normative, evaluative, motivational, and active. The activity of the future teacher of physical education at different stages of pedagogical activity depends on many objective and subjective factors. It manifests itself in such areas of public life: educational activities, fitness activities, social activities, self-educational activities, labor activities